STATCOM with Battery and Super Capacitor Hybrid Energy Storage System for Enhancement of Voltage Stability - Tanneeru Renuka; Gattu Kesavarao (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
To maintain voltage stability of a power system STATCOM is better solution which can provide the required amount of reactive power under various disturbances. In previous work, STATCOM with various energy storage elements was discussed for voltage and power system stability. Apart from these previous works, this work proposes a new structure of hybrid energy storage system (HESS) for voltage stability by using battery and super capacitor. A new model of STATCOM with hybrid energy storage system is designed by using two bidirectional DC-DC converters and results are analyzed for conventional STATCOM and STATCOM with hybrid energy storage system. Results are also analyzed for STATCOM system with out any energy storage system, STATCOM with battery, STATCOM with super capacitor and STATCOM with HESS under sudden load changes by using MATLAB/Simulink.